2014
DOI: 10.3109/08958378.2014.970783
|View full text |Cite
|
Sign up to set email alerts
|

Health effects after firing small arms comparing leaded and unleaded ammunition

Abstract: A number of Norwegian soldiers have reported health problems after live-fire training using the HK416 rifle. The objective of this study was to characterize gaseous and particulate emissions from three different types of ammunition, and record the health effects after exposure to emissions from live-firing. Fifty-five healthy, non-smoking men (mean age 40 years) were recruited and divided randomly into three groups, one for each type of ammunition. All subjects fired the HK416 rifle in a semi-airtight tent for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 18 publications
5
27
0
Order By: Relevance
“…This is supported by a recent study of particles emitted when firing Pb-free and standard 5.56-mm ammunition, where most of the metals were reported to be in the form of metal oxides associated to soot (Voie et al, 2014). Once in contact with cells, studies found that nanosized sintered metal oxides, that is, metal oxides produced in hightemperature processes, are taken up by cells and that they then release metal ions within cells (Brunner et al, 2006;Grass et al, 2010;Raemy et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…This is supported by a recent study of particles emitted when firing Pb-free and standard 5.56-mm ammunition, where most of the metals were reported to be in the form of metal oxides associated to soot (Voie et al, 2014). Once in contact with cells, studies found that nanosized sintered metal oxides, that is, metal oxides produced in hightemperature processes, are taken up by cells and that they then release metal ions within cells (Brunner et al, 2006;Grass et al, 2010;Raemy et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, as already mentioned, recent experiments on acute exposure to gases and aerosols from ammunition, both conventional and Pb-free, indicate immediate health issues including respiratory irritation, metal fume fever, and nausea and more symptoms were associated with Pb-free ammunition than with the conventional kind (Strømseng et al, 2009;Voie et al, 2014). These findings emphasize the need for more data on this new type of ammunition.…”
mentioning
confidence: 54%
See 3 more Smart Citations